2014
DOI: 10.1097/sle.0b013e3182937fe8
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics Problems Due to the Use and Design of Dissector and Needle Holder

Abstract: As far as we know, this is the largest Spanish survey conducted on this topic. From this survey, some ergonomic drawbacks have been identified in: (a) the instruments' design, (b) the operating tables, and (c) the posture of the surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Laparoscopic instruments are known to cause physical discomfort [15, 16] and, moreover, to cause injuries especially affecting the thumbs [17, 18]. Furthermore, almost all laparoscopic handles come with the adage “one size fits all” whereas small hand size is a known risk factor for experiencing physical discomfort and difficulties in the use of laparoscopic instruments [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic instruments are known to cause physical discomfort [15, 16] and, moreover, to cause injuries especially affecting the thumbs [17, 18]. Furthermore, almost all laparoscopic handles come with the adage “one size fits all” whereas small hand size is a known risk factor for experiencing physical discomfort and difficulties in the use of laparoscopic instruments [1921].…”
Section: Introductionmentioning
confidence: 99%
“…The instrument handle is an essential part of laparoscopic instruments, whose inappropriate design can have a detrimental effect on the surgeon's efficiency and wellbeing [33]. The rate of work-related musculoskeletal disorders in laparoscopy are from 73% to 100%, with poor instrument handle design being one of the main risk factors [34,35]. In a survey by Santos-Carreras et al, they assessed the acceptance of different surgical instrument handle designs and they reported that conventional laparoscopic instrument handles such as the axial handle scored lowest in terms of comfort [36].…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder, neck, back, and hand pain and stiffness were reported as the main physical symptoms during laparoscopic procedures [36,37]. The surgeon's height, glove size, age, gender, type of instrument, foot pedals, and height of the operating table have been identified as important factors for increasing the musculoskeletal pain symptoms [38][39][40][41]. The shape of the laparoscopic instrument handle was identified as the main element that needed to be improved [40].…”
Section: Questionnairesmentioning
confidence: 99%